ANALYSIS OF GREEN ACCOUNTING IMPLEMENTATION, ESG DISCLOSURE, PRICE TO BOOK VALUE AND THEIR IMPACT ON COMPANY PERFORMANCE IN THE MINING SECTOR FOR THE PERIOD 2022-2023 - ILLIYYA RAYATA ARDHANI; Putri Dwi Rahmawati; Nindita Fitria Ariyanto (Journal of Strategic Behaviour Accounting, 2025)
This study examines the extent to which the implementation of green accounting, Environmental, Social, and Governance (ESG) disclosure, and Price-to-Book Value (PBV) affect the performance of mining sector companies listed on the Indonesia Stock Exchange (IDX) during 2022–2023. Green accounting reflects a company’s environmental management commitment, ESG represents social and governance responsibility, while PBV indicates market perception of a firm’s value. Using a quantitative approach with secondary data from financial statements and sustainability reports, this research analyzes the influence of these variables on company performance measured by Return on Assets (ROA).The findings show that green accounting, ESG disclosure, and PBV do not significantly affect financial performance either partially or simultaneously. These results suggest that sustainability practices in Indonesia’s mining sector are still in their early stages and have yet to translate into short-term financial benefits. However, they provide a foundation for the gradual integration of sustainability principles into corporate decision-making and long-term strategic planning.